Obesity is Associated with Higher Blood Pressure and Higher Levels of Angiotensin II but Lower Angiotensin-(1-7) in Adolescents Born Preterm - South, Andrew M. (J Pediatr, 2018)
OBJECTIVES: To evaluate if obesity is associated with increased angiotensin II (Ang II) and decreased angiotensin-(1–7) [Ang-(1–7)] in the circulation and urine among adolescents born prematurely. STUDY DESIGN: In a cross-sectional analysis of 175 14-year-olds born preterm with very low birth weight, we quantified plasma and urinary Ang II and Ang-(1–7) and compared their levels between subjects with overweight/obesity (body mass index ≥85(th) percentile, n = 61) and those with body mass index <85(th) percentile (n = 114) using generalized linear models, adjusted for race and antenatal corticosteroid exposure. RESULTS: Overweight/obesity was associated with higher systolic blood pressure and a greater proportion with high blood pressure. After adjustment for confounders, overweight/obesity was associated with an elevated ratio of plasma Ang II to Ang-(1–7) (β: 0.57, 95% CI 0.23 to 0.91) and higher Ang II (β: 0.21 pmol/l, 95% CI 0.03 to 0.39) but lower Ang-(1–7) (β: −0.37 pmol/l, 95% CI −0.7 to −0.04). Overweight/obesity was associated with a higher ratio of urinary Ang II to Ang-(1–7) (β: 0.21, 95% CI −0.02 to 0.44), an effect that approached statistical significance. CONCLUSIONS: Among preterm-born adolescents, overweight/obesity was associated with increased Ang II but reduced Ang-(1–7) in the circulation and the kidney as well as higher blood pressure. Obesity may compound the increased risk of hypertension and cardiovascular disease in individuals born prematurely by further augmenting the prematurity-associated imbalance in the renin-angiotensin system.